Spaces and Imaginaries of the Metaverse The Myth of the Virtuality of the Internet at Horizon - Biggio, Federico (Funes. Journal of narratives and social sciences, 2026)
This article examines how contemporary imaginaries of the metaverse inherit and reshape the twentieth-century myths of virtual reality and the early Internet. Bringing together philosophy, media theory, and sociotechnical history, the paper traces and reframes virtuality and “immersion” as a threshold experience linked to deterritorialization. Adopting a critical and political perspective, the analysis highlights how the metaverse functions as a “third space”: an arena of playful interaction and creative experimentation, but also one shaped by technopolitical asymmetries and the remediation of social media logics in immersive 3D environments. Historical parallels with the commercialization of the Web and world expositions reveal how colonial and capitalist tropes persist in promises of frictionless transcendence. The article mobilizes concepts of code/space, smooth/striated space, and user practice to show how platform architectures reterritorialize the “virtuality” they advertise. Ultimately, the paper contends that the myth of the metaverse’s virtuality conceals a process of reterritorialization, where the utopian promises of cyberspace give way to the controlled architectures of platform capitalism, turning the dream of virtual worlds into an infrastructural and ideological extension of the Internet’s history.